Effects of intracellular calcium ions in causing apoptosis of Hep-G2 liver cell lines after infection with Leptospira interrogans - Mohd Hafiz Ngoo, Muhamad Sofie (2018)
Leptospirosis, is a zoonotic disease in mammals caused by pathogenic Leptospira sp.The most virulent species among pathogenicLeptospira sp. is Leptospira interrogans. Many features of its pathogenesis are still unknown. Calcium ions play a role as a secondary messenger in all living cells. However, level of calcium ions exceeding normal cellular threshold can cause activation of calpain leading to cell death, degradation of cytoskeletal structures and diseases progression. Cases with dogs infected with pathogenic Leptospira sp., the infection is acute and most dogs die in a week after contraction. This study aims to identify the effect of intracellular calcium ions in the progression of L. interrogans infection onto Hep-G2 cell line. Cell mortality was observed with Acridine orange and propidium iodine (AO/PI) stain and examined under fluorescence microscope. Cell mortality percentage were quantified with ImageJ software. Following L. interrogans infection on Hep-G2 cells, infected cells were withdrawn at interval period of 30 minutes, 1 hour, 3 hours and 6 hours post infection. Transmission electron microscope (TEM) and scanning electron microscope (SEM) were used to identify the infiltration of L. interrogansinto Hep-G2 cells. Apoptosis markers (pro-caspase-3) were detected via fluorescence microscope. Intracellular calcium ions were detected using Abcam calcium ions detection kit. The expression of calpain-1 gene was assessed by using reverse transcription PCR. During AO/PI analysis, L. interrogans were seen attached to cells that are clumping with high intercellular tight junctions.Mortality of Hep-G2 cells throughout the infection for multiplicity of infection (MOI) 10 (M = 16.87, SD = 9.06) was significantly lower than MOI 100. MOI 100 showed a higher degree of mortality at 30 minutes infection. SEM and TEM analysis provided evidence of infiltration and also the formation of cell “blebbing” during Hep-G2 infection with L. interrogans. Pro-caspase-3 activity of Hep-G2 cells were detected during 30 minutes infection. Post infection period of 30 minutes, 1 hour, 3 hours and 6 hours shown decreased levels of calcium ions compared to control counterpart. Calpain-1 was detected at 1 hour post infection. As a conclusion, infection of L. interroganson Hep-G2caused the decrease of calcium ion in Hep-G2 cellswhich is linked to the activation of calpain-1. Calpain-1 then promotes cytoskeletal degradation (cell “blebbing”) leading to the loss of cell integrity and apoptosis of the infected host cells.